Investigation on wear characteristic of biopolymer gear - Wafiuddin, Md Ghazali; Daing Mohamad Nafiz, Daing Idris; Azizul Helmi, Sofian; F., Basrawi; Thamir K., Ibrahim (2017)
Polymer is widely used in many mechanical components such as gear. With the world going to a more green and sustainable environment, polymers which are bio based are being recognized as a replacement for conventional polymers based on fossil fuel. The use of biopolymer in mechanical components especially gear have not been fully explored yet. This research focuses on biopolymer for spur gear and whether the conventional method to investigate wear characteristic is applicable. The spur gears are produced by injection moulding and tested on several speeds using a custom test equipment. The wear formation such as tooth fracture, tooth deformation, debris and weight loss was observed on the biopolymer spur gear. It was noted that the biopolymer gear wear mechanism was similar with other type of polymer spur gears. It also undergoes stages of wear which are; running in, linear and rapid. It can be said that the wear mechanism of biopolymer spur gear is comparable to fossil fuel based polymer spur gear.